Chronic obstructive pulmonary disease hospitalisations and mortality in Victoria: analysis of variations by socioeconomic status - Timothy Ore; Paul Ireland (Elsevier, 2015)
Abstract Objective: This paper analysed chronic obstructive pulmonary disease (COPD) hospitalisations, unplanned readmissions and deaths in Victoria to identify associations with socioeconomic status (SES). Methods: The data was taken from the Victorian Admitted Episodes Dataset, the Victorian Health Information Surveillance System, the Victorian Burden of Disease Study and the Australian Bureau of Statistics' Index of Relative Socioeconomic Disadvantage. Results: COPD separations have a greater variation by SES than all separations. The average age‐standardised separation rate (10.43) for the top percentile Local Government Areas (LGA) was 5.8 times that of the bottom percentile LGAs (1.80). The top percentile group was the lowest SES group (effect size = 0.93). There were significant negative correlations between the age‐standardised COPD separation rates and SES across LGAs (r = −0.60) and Regions (r = −0.89). Analysis of readmissions (r = −0.49), mortality data (r = −0.51) and the burden of disease data (r = −0.39) also showed significant inverse associations between COPD and SES. Conclusions and implications: Victorians living in the most disadvantaged areas have a greater burden from COPD, highlighting a need to prioritise public health services interventions to improve outcomes.